![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(2x-35=15\)
\(\Rightarrow2x=15+35\)
\(\Rightarrow2x=50\)
\(\Rightarrow x=\frac{50}{2}=25\)
Vậy : \(x=25\)
\(3x+17=2\)
\(\Rightarrow3x=2-17\)
\(\Rightarrow3x=-15\)
\(\Rightarrow x=-\frac{15}{3}=-5\)
Vậy: \(x=-5\)
\(\left|x-1\right|=0\)
\(\Rightarrow x-1=0\)
\(\Rightarrow x=0+1=1\)
a)2x-35=15
2x =15+35
2x =50
x =50:2
x =25
b)3x +17=2
3x =17-2
3x =15
x =15:3
x =5
c)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)-(2x + 15 ) + 13 = -234
\(\Leftrightarrow\)-2x-15+13+234=0
\(\Leftrightarrow\)2x=232
\(\Leftrightarrow\)x=116
b)2+4+6+8 +..............+2x=182
\(\Leftrightarrow\)2(1+2+3+4+.....+x) =182
\(\Leftrightarrow\)1+2+3+4+.....+x= 182/2 = 91
\(\Leftrightarrow\)x(x+1)/2 =91
\(\Leftrightarrow\)x(x+1)= 182
\(\Leftrightarrow\)x(x+1) = 13(13+1)
\(\Leftrightarrow\)\(\hept{\begin{cases}x=13\\x+1=13+1\end{cases}}\Leftrightarrow x=13\)
Vậy...
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(x-\left(-234\right)=766\)
\(x=766+\left(-234\right)\)
\(x=532\)
b) \(2017-\left(17-x\right)=4016\)
\(17-x=2017-4016\)
\(17-x=\left(-1999\right)\)
\(x=17-\left(-1999\right)\)
\(x=2016\)
c) \(\left|x-1\right|=5\)
\(\left|x\right|=5+1\)
\(\left|x\right|=6\)
\(\Rightarrow x=6\)
d) \(\left(2x+1\right)^2=9\)
\(x=1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x + 118 = 218
x = 218 – 118
x = 100
b) 18 – x = -17
X = 18 – (-17)
X = 35
c) (-18) – x = -17
X = (-18) – (-17)
X = -1
d)124 + (118 – x) = 217
118 – x = 93
X = 118 – 93
X = 25
e) (3x – 6).3 = 34
(3x – 6).3 = 81
3x – 6 = 27
3x = 33
ð X = 11
g) 23.(42 – x) = 46
42 – x = 2
ð X = 40
h) 84 – (3x + 8) = 34
3x + 8 = 84 – 34
3x + 8 = 50
3x = 50 – 8
3x = 42
X = 42 : 3
ð X = 14
i) 3.(2x + 1) – 19 = 14
3.(2x + 1) = 14 + 19
3.(2x + 1) = 33
2x + 1 = 33 : 3
2x + 1 = 11
2x = 11 – 1
2x = 10
X = 10 : 2
ð X = 5
k) 6x – 302 = 23.5
6x – 302 = 40
6x = 40 + 302
6x = 342
X = 342 : 6
ð X = 57
m) (x – 1)2 = 81
(x – 1)2 = 92
ð X – 1 = 9
ð X = 9 + 1
ð X = 10
n) 2x+1 – 5 = 27
2x+1 = 27 + 5
2x+1 = 32
2x+1 = 25
ð X = 4
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x - 3 + (5 + 3) = 3 - (6 - 4)
<=> x - 3 + 8 = 1
<=> x + 5 = 1 => x = - 4
b) 3 - (x - 6) + (2x - 4) = 11
<=> 3 - x + 6 + 2x -4 = 11
<=> x + 5 = 11 => x = 6
c) 17 - 2x - (3 - x - 17) = 6
<=> 17 - 2x - 3 + x + 17 = 6
<=> - x + 31 = 6
<=> - x = - 25 => x = 25
a. x-3+(5+3)=3-(6-4
x-3+8=3-2
x-3+8=1
x-3=1-8
x-3=-7
x=-7+3
x=-4
![](https://rs.olm.vn/images/avt/0.png?1311)
a/\(-\left(-432-3x\right)+\left(-432-4x+21\right)=-2345\)
\(\Leftrightarrow+432+3x-432-4x+21=-2345\)\(\Leftrightarrow\left[432+\left(-432\right)\right]+\left[\left(-4x\right)+3x\right]+21=-2345\)
\(\Leftrightarrow0+-1x+21=-2345\)\(\Leftrightarrow-1x=-2345-21=-2366\)
\(\Rightarrow x=\left(-2366\right):\left(-1\right)=2366\)
b/\(12x-\left(-3546-3x\right)=\left(2x-234\right)-\left(-678-2x\right)\)
\(\Leftrightarrow12x+3546+3x=2x-234+678+2x\)
\(\Leftrightarrow15x+3546=\left(2x+2x\right)+\left[\left(-234\right)+678\right]\)
\(\Leftrightarrow15x+3546=4x+444\)
\(\Leftrightarrow15x+3546-4x-444=0\)
\(\Leftrightarrow\left(15x-4x\right)+\left(3546-444\right)=0\)
\(\Leftrightarrow11x+3102=0\)
\(\Leftrightarrow11x=0-3102=-3102\)
\(\Rightarrow x=\left(-3102\right):11=-282\)
![](https://rs.olm.vn/images/avt/0.png?1311)
phá ngoặc lun nà:
2x-(234-(-456-543-3x))=23
2x-(234+456+543+3x)=23
2x-234-456-543-3x=23
-x-1233=23
-x=23+1233=1256
x=1256
![](https://rs.olm.vn/images/avt/0.png?1311)
1) 13-(x-7)=5
<=> 13 - x + 7 = 5
<=> x = 15
2) /x/=2015 => x = 2015 hoặc x = -2015
3) 2x+17=15+x
<=> x = -2
4) 2x-9=-17
<=> 2x = -8
<=> x = -4
234-4x(2x+17)=118
4x(2x+17)=234-118
4x(2x+17)=116
(2x+17)=116:4
(2x+17)=29
2x =29-17
2x =12
x =12:2
x = 6
234 - 4 . ( 2x + 17 ) = 188
4 . ( 2x + 17 ) = 234 - 188
4 . ( 2x + 17 ) = 116
( 2x + 17 ) = 116 : 4
( 2x + 17 ) = 29
2x = 29 - 17
2x = 12
x = 12 : 2
x = 6